2010
DOI: 10.1175/2010jcli3389.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of the Atlantic Meridional Overturning Circulation at 26.5°N

Abstract: The Atlantic meridional overturning circulation (AMOC) makes the strongest oceanic contribution to the me ridional redistribution of heat. Here, an observation-based, fortyeight-month-long time series of the vertical structure and strength of the AMOC at 26.5°N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
360
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(411 citation statements)
references
References 61 publications
47
360
3
1
Order By: Relevance
“…The North Atlantic Deep Water (NADW) cell of the AMOC peaks at 17.0 Sv (1 Sv = 10 6 m 3 s −1 ) at 32.5 • N and a depth of 1020 m. This agrees with the estimate of 16 ± 2 Sv from Ganachaud (2003) and recent measurements of 18.7±2 Sv at 26.5 • N (Kanzow et al, 2010). The NADW is formed south of Greenland and in the Nordic seas (Fig.…”
Section: The Pre-industrial Oceansupporting
confidence: 86%
“…The North Atlantic Deep Water (NADW) cell of the AMOC peaks at 17.0 Sv (1 Sv = 10 6 m 3 s −1 ) at 32.5 • N and a depth of 1020 m. This agrees with the estimate of 16 ± 2 Sv from Ganachaud (2003) and recent measurements of 18.7±2 Sv at 26.5 • N (Kanzow et al, 2010). The NADW is formed south of Greenland and in the Nordic seas (Fig.…”
Section: The Pre-industrial Oceansupporting
confidence: 86%
“…In comparison, Kanzow et al [2010] derive 18.7˙2.1 Sv from observations. We conclude that an increased zonal diffusivity improves the model, but expressed as global metrics, does little to change the physics.…”
Section: Resultsmentioning
confidence: 92%
“…590 Y. Fu et al: AMOC at 14.5 • N and 24.5 • N MOCHA-WBTS, hereafter RAPID) have shown that the AMOC exhibits variability on timescales from seasonal to decadal (Cunningham et al, 2007;Kanzow et al, 2008Kanzow et al, , 2010Smeed et al, 2014). At 26 • N, different components of the AMOC have been analyzed in detail including the western boundary current (Florida Current), the Ekman transport, and the interior geostrophic transport.…”
Section: Introductionmentioning
confidence: 99%
“…At 26 • N, different components of the AMOC have been analyzed in detail including the western boundary current (Florida Current), the Ekman transport, and the interior geostrophic transport. Based on the RAPID array data, Cunningham et al (2007) reported that on subseasonal timescales, the upper ocean has an immediate response to the change in the Ekman transport, while Kanzow et al (2010) showed that on seasonal timescales, the wind stress curl near the eastern boundary plays a dominant role in modulating the strength of the AMOC. Interestingly, studies based on the RAPID array at 26 • N and on the MOVE array at 16 • N often reveal contrary conclusions on the AMOC.…”
Section: Introductionmentioning
confidence: 99%